UNDER STARVED CONDITIONS THE EXPRESSION PATTERN OF HYPOTHALAMIC KISSPEPTIN/GPR54 AND ROLE OF KISSPEPTIN-10 IN RESTORATION OF LH SECRETION IN PREPUBERTAL EWES - J. Wang; L. Sun; T. Zhang; H.Zhou; J. Xu; Y. Lou (Journal of Animal and Plant Sciences, 2014)
Kisspeptin and its receptor G protein-coupled receptor (GPR54) have been shown to play a crucial role in regulation of GnRH secretion. The objective of this study was to evaluate the role of Kisspeptin/GPR54 in inhibition of LH secretion of prepubertal ewe sunder feed restricted conditions. Three months old, female, Small Tail Han sheep, around 16.2 kg body weights were used in this study. During experiment I, in control group, ewes were fed with standard diet (n=4), while in feed restricted group, ewes were subjected to 40% restriction in daily feed intake (n=4). Thirty days later, blood serum and hypothalamus of all the animals were obtained to determine secretion level of LH, insulin, leptin and expression of KiSS-1 and GPR54. The results showed that feed restriction significantly decreased hypothalamic expression of KiSS-1 (P<0.01) and serum concentration of LH (P<0.05), insulin (P<0.05) and leptin (P<0.01) in prepubertal ewes. In experiment II, the same animals underfeed restriction were injected with 1mg of kisspeptin-10 (n=4; treatment group), and normal saline (n=4; control group). Serial blood samples were collected at 15-min intervals for 180 min to analyze the response curve of LH secretion after injection. The results showed that in prepubertal ewes under feed restriction injection with kisspeptin-10 significantly increased the LH secretion (P<0.01). The results indicate that the inhibitory effect of long-term feed restriction on LH secretion in prepubertal ewes is possibly because of a decrease in hypothalamic expression of KiSS-1.
Keywords: Feed restriction; LH; Kisspeptin/GPR54Prepubertal ewes